ANALISIS PERMINTAAN DAN PENAWARAN UANG DI INDONESIA - Arwin Arwin; Said Muhammad; Raja Masbar (Jurnal Perspektif Ekonomi Darussalam (Darussalam Journal of Economic Perspec, 2019)
This study aims to determine the determinants of the money demand and money supply function in Indonesia. To formulate the equation between money demand (Md) and money supply (Ms) using LM function by looking at the effect of real income and interest rate. The data in this study constitutes Indonesia's economic data from 1986 to 2015 drawn from secondary data sources such as Bank Indonesia (BI), Central Bureau of Statistics (BPS), International Financial Statistics (IFS), International Monetary Funds (IMF) and World Bank . The Data Processing method used is to use the equations and completed with Two Stage Least Square. The results showed that the balance occurred at the national income level of 277559.05 billion Rupiah with an interest rate of 7.05%. Keywords: Demand and Supply of Money, Gross Domestic Product, Interest Rate, Inflation, and Exchange Rate. Abstrak Penelitian ini bertujuan untuk megetahui determinan dari fungsi permintaan uang dan penawaran uang di Indonesia. Untuk merumuskan persamaan antara permintaan uang (Md) dengan penawaran uang (Ms) menggunakan fungsi LM dengan melihat pengaruh pendapatan riil dan tingkat suku bunga. Data dalam penelitian ini merupakan data perekonomian Indonesia dari tahun 1986 – 2015 yang diambilkan dari sumber data sekunder baik seperti Bank Indonesia(BI), Badan Pusat Statistik (BPS), Internasional Financial Statistics (IFS), International Monetary Funds ( IMF) dan World Bank. Metode Pengolahan datayang digunakan adalah menggunakan persamaan simultan dan diselesaikan dengan Two Stage Least Square. Hasil penelitian menunjukkan bahwa keseimbangan terjadi pada tingkat pendapatan nasional sebesar 277559.05 milyar Rupiah dengan tingkat bunga sebesar 7,05%.